Breaking Barriers: Advancing Inclusive Education Through Early Identification of Learning Challenges - Dukha Yunitasari; I Wayan Lasmawan; Ida bagus Putu Arnyana; I Made Ardana (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
This study aims to identify the profiles of students with functional learning disabilities in 30 schools (Elementary Schools/Madrasah Ibtidaiyah) in Lombok Timur, Indonesia, as well as to explore the challenges faced by teachers and principals in providing appropriate interventions. The research methodology employed data analysis from questionnaires, interviews, and Focus Group Discussions with 120 teachers from Elementary Schools/Madrasah Ibtidaiyah. The analysis results indicate that out of a total of 2763 registered students, 283 students experience functional learning disabilities, with the majority being female students (58%) and male students (42%). Cognitive and dyslexia-related disabilities are the most common types of disabilities, followed by behavioural and emotional disabilities. Teachers and principals encounter difficulties in providing appropriate and effective interventions for these students with special needs. Based on the results of the analysis, it is concluded that concerted efforts are required among schools, teachers, parents, and various stakeholders to develop more effective inclusive education strategies. Recommended steps include providing additional training for teachers, creating more structured student support programs, and enhancing communication between schools and parents.